2022
DOI: 10.1016/j.yexcr.2021.112906
|View full text |Cite
|
Sign up to set email alerts
|

Defining and identifying satellite cell-opathies within muscular dystrophies and myopathies

Abstract: Muscular dystrophies and congenital myopathies arise from specific genetic mutations causing skeletal muscle weakness that reduces quality of life. Muscle health relies on resident muscle stem cells called satellite cells, which enable life-course muscle growth, maintenance, repair and regeneration. Such tuned plasticity gradually diminishes in muscle diseases, suggesting compromised satellite cell function. A central issue however, is whether the pathogenic mutation perturbs satellite cell function directly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 238 publications
(308 reference statements)
1
40
0
Order By: Relevance
“…Piezo1 s importance in skeletal muscle maintenance and function will undoubtedly grow as new research aims to explore the mechanisms and signalling pathways this remarkable mechanosensor employs. Moreover, given Piezo1's pivotal role in myogenic progression and its expression in satellite cells, it is likely that altered Piezo1 activity may associate with pathogenesis of satellite cell-opathies [37].…”
Section: Discussionmentioning
confidence: 99%
“…Piezo1 s importance in skeletal muscle maintenance and function will undoubtedly grow as new research aims to explore the mechanisms and signalling pathways this remarkable mechanosensor employs. Moreover, given Piezo1's pivotal role in myogenic progression and its expression in satellite cells, it is likely that altered Piezo1 activity may associate with pathogenesis of satellite cell-opathies [37].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, DUX4-induced alteration in WNT/β-CATENIN signalling would also contribute to inefficient muscle regeneration in FSHD ( Banerji et al, 2020b ). We recently defined FSHD as a secondary Satellite Cell-opathy ( Ganassi et al, 2022 ; Ganassi and Zammit, 2022 ), given that DUX4 affects both satellite cell/myoblast and muscle fibre function, and suppression of PAX7 target genes ( Banerji et al, 2017 ; Banerji and Zammit, 2021 ). Here, we found that DUX4-mediated activation of β-CATENIN signalling does not promote a coordinated ‘myogenic differentiation’ transcriptome.…”
Section: Discussionmentioning
confidence: 99%
“…Defects in cell-cell fusion are involved in infertility ( 34 ), preeclampsia ( 35 ), osteoporosis ( 36 ), cancer ( 37 ), and infection ( 10 , 38 ). In skeletal muscle, alterations in myoblast fusion have been reported to contribute to the pathology of human neuromuscular diseases ( 39 , 40 ) such as Duchenne muscular dystrophy ( 41 , 42 ), limb-girdle muscular dystrophy ( 43 ), and Emery-Dreifuss muscular dystrophy ( 44 ). The discovery of pathogenic variants in MYMK and MYMX highlights a new form of fusogenic myopathy.…”
Section: Discussionmentioning
confidence: 99%